EFFECT OF SAWDUST USAGE ON THE SHEAR STRENGTH BEHAVIOR OF CLAYEY SILT SOIL - Jasim, Omar Hamdi; Cetin, Dogan (YILDIZ TECHNICAL UNIV, 2016)
The aim of this paper is to study the effect of sawdust content on the engineering properties of clayey-silt soil. Soil from the district of Buyukcekmece in Istanbul city have been used. Its engineering properties were indicated. The dry soil passing sieves No. 40 were mixed with the sawdust, with the amount 1, 2, 3 and 5 % from dry weight of soil, then, samples engineering properties were indicated. The study concluded that the addition of sawdust up to 5% decreased the liquid limits and the plasticity index by 14.9% and 17.6% respectively, and also decreased the plastic limits by 13.15%. Effect of sawdust usage on undrained shear strength of the soil were investigated by unconfined compression test and UU triaxial test. The undrained strength were increased by 41.437% with increasing 3 % but, the undrained strength decreased with 5% of sawdust. Also the results obtained from unconfined compression test and UU triaxial test were compared and looked at compatibility of the results.
Keywords: Undrained Shear Strength; sawdust; triaxial test; unconfined compression test; Engineering